A Study on IIIA Group Metals (B or Ga or Tl) Doped Mo2C-HZSM-5 Catalysts for Methane Dehydroaromatization - Nagaraju Pasupulety; Majed A. Alamoudi; Abdulrahim A. Al-Zahrani (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
Methane dehydroaromatization (MDA) is a promising route for direct conversion of methane into value-added aromatics such as benzene, toluene and naphthalene. This study investigates the effect of IIIA group metals like boron (B), gallium (Ga), and thallium (Tl) doped into Mo₂C/HZSM-5 catalysts tested for MDA at 700 oC and 1800 mL.gcat-1.h-1. The influence of promoters on catalyst acidity and coke formation was investigated through various analytical techniques including NH₃-TPD and TPO. Among the samples, Ga-Mo₂C/HZSM-5 demonstrated greater benzene selectivity and consistent stability due to abundant Mo2C and low temperature coke formations. Whereas, B- or Tl-Mo₂C/HZSM-5 suffered from high temperature coke formations related to their greater acidity and greater extent of surface molybdenum oxidized species. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).